Fluid Dynamics and Simulation Study of Particles Inside of a Hydrocyclone Using Comsol - Manriquez-Fica, J; Cifuentes-Molina, G (Italian Association of Chemical Engineering - AIDIC, 2017)
The parameters that define the performance of the hydrocyclone in mineral size reduction circuits are the profile of selectivity of the size of ore pulp in discharge and the overflow from hydrocyclone, along with the velocity field of the pulp to the interior of this reactor. The dynamical behaviour of the hydrocyclone and the particle size of the final product in 3D using COMSOL Multiphysics were studied in this article. The fluid is governed by the continuity and the conservation of the momentum equations, in addition to the k-e turbulence model. Studies were performed on a hydrocyclone of 75 [mm], and a flow of pulp of 4.88% solids by weight. The simulation presented results suitable for particle sizes greater than 17.74 [μm], within a range of 9 to 35.5 [μm]. For lower sizes, selectivity curve presents problems since the turbulence model is not suitable for modelling the ascending secondary vortex in the hydrocyclone. © Copyright 2017, AIDIC Servizi S.r.l.